MORPHOLOGY OF EXCRETORY TISSUE OF LEAVES AND SECONDARY METABOLITES OF SOME SPECIES FROM INULA GENUS - Aida Ya. Tamakhina; Angela A. Gadiyeva (Юг России: экология, развитие, 2017)
Aim. This work is devoted to studying the morphology of the excretory tissue of leaves and secondary metabolites of some species from Inula genus (Inula britannica L., Inula aspera Poir., Inula germanica L.) grown in plant communities of the foothill and steppe zones of the Kabardino-Balkar Republic. Methods. As object of a research served the leaves of an average tier of plants collected in a phase of the complete blossomingin August, 2015-2016. Applied the standard histochemical test reactions to identification of secondary metabolites. Results. Morphological structure of non-glandular trichomes are typical of the Asteraceae family. Hairs are located on large veins and interveinal region abaxial, rarely adaxial surface of the leaf. The total number of non-glandular trichomes decreases among I. britannica L. – I. aspera Poir. – I. germanica L. Glandular trichomes are located on the abaxial surface of the leaf and have morphological species characteristics. The number of glandular trichomes per 1 mm2 of the leaf surface varies from 1 (I. germanica L.) to 16 (I. aspera Poir.). In the leaves of I. germanica L. are formed endogenous secretory structures: schizogenous intercellular spacese, idioblast, latex vessel. The secondary metabolites of I. britannica L. are essential oils, I. germanica L. – essential oils, resins, calcium oxalate, rubber, I. aspera Poir. – essential oils, resins, polysaccharides. Conclusion. Morphological features of secretory tissue and chemical composition of secondary metabolites in the leaves of the genus Inula L. due to the influence of abiotic conditions and associated with the ecological strategy of the species. Differences in the morphology of glandular structures can be used for micro-diagnostics species of the genus Inula L.